TRADE ORIENTATION IN THE EU IN THE AFTERMATH OF THE FINANCIAL CRISIS - Cristian SPIRIDON (CES Working Papers, 2014)
The present paper aims to analyze the impact the economic crisis bursted out in the United States at the end of 2007 and quasi spreaded all over the world had on the (re) orientation of trade flows (exports) among European Union member states in general, and Romania in particular. As observation and analysis data tool we chose groupings, tabular and graphical representation. The analysis will be conducted at individual and group of countries levels. The main findings will show that although the geographic network of member states trade has been seriously shaken by the crisis, export flows orientatio remained quite similar to the period previous to economic decline. As for Romania, its exports prove to be influenced by the economic situation of the main European partners.